2017
DOI: 10.3892/mmr.2017.7667
|View full text |Cite
|
Sign up to set email alerts
|

The effect of anagliptin on intimal hyperplasia of rat carotid artery after balloon injury

Abstract: The present study evaluated the effect of anagliptin on intimal hyperplasia following carotid artery injury in Sprague-Dawley rats. Sprague-Dawley rats weighing 280–300 g were injured using a 2F Fogarty balloon embolectomy catheter. The rats were divided into injury-(saline) and anagliptin-(10 mg/kg/day) treated groups. vascular injuries were induced in the left carotid artery, followed by evaluation of neointima formation at 28 days. The right and left carotid arteries were harvested and evaluated with histol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…In addition, a report from Li et al. showed that anagliptin, the DPP-4 inhibitor, attenuated neointima formation in rats suffered balloon injury by preventing the production of inflammatory cytokines and chemokines [18]. In agreement with these studies, we found that the levels of TNF-α, IL-1β and IL-6 in the cervical aorta of rats were increased after balloon injury, and linagliptin inhibited the production of these inflammatory factors dose dependently.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, a report from Li et al. showed that anagliptin, the DPP-4 inhibitor, attenuated neointima formation in rats suffered balloon injury by preventing the production of inflammatory cytokines and chemokines [18]. In agreement with these studies, we found that the levels of TNF-α, IL-1β and IL-6 in the cervical aorta of rats were increased after balloon injury, and linagliptin inhibited the production of these inflammatory factors dose dependently.…”
Section: Discussionsupporting
confidence: 90%
“…In a murine atherosclerosis model, the treatment of mice with anagliptin reduced aortic plaque burden [9]. In induced vascular injury rats, administration of anagliptin reduces neointimal formation and relieves whole-body inflammation [10]. In a vascular aneurysm model, the treatment of animals by anagliptin significantly reduces the size of intracranial aneurysms and suppresses inflammatory pathway in macrophages [11].…”
Section: Introductionmentioning
confidence: 99%
“…In normal adult, VSMCs maintains a contractile phenotype which proliferates slowly and expresses a range of contractile proteins for functional contraction. In response to vascular injury or local environmental alteration, contractile VSMCs dedifferentiate to synthetic phenotype ( Allahverdian et al, 2018 ), characterized as repressed contractile proteins, altered morphology from elongated/spindle-like to thomboid/epitheloid-like, increased proliferation, and facilitated migration ( Li et al, 2017 ). In healthy vascular wall, individual VSMC dedifferentiation occurs at a low event rate which participates in vascular wall repair.…”
Section: Discussionmentioning
confidence: 99%